Peningkatan Literasi Keuangan Digital dalam Upaya Meminimalkan Korban Pinjaman Online - Novi Trisnawati; Puji Handayati (Idea Pengabdian Masyarakat, 2022)
Financial Technology (FinTech) is one of the financial innovations that comes as a result of technological developments. One type of fintech is Peer-to-Peer (P2P) Lending or information technology-based loan services (online loans). Until 2021, many borrowing entities have sprung up, in fact there have been 3,516 illegal online loan entities that have been closed by the OJK. This is also the cause of many cases of public complaints related to online loans. This phenomenon is caused by the lack of digital financial literacy among the public. To reduce or minimize victims or cases resulting from online loans, it is necessary to increase digital financial literacy in the community. The purpose of this Community Service activity is to improve people’s digital financial literacy. The target subjects in this activity are the villagers of Kejapanan, Gempol, Pasuruan, especially housewife. The method used to convey digital financial literacy is through socialization where in addition to the team delivering material, there is also a question and answer session with the socialization participants. The socialization process went well and received quite good feedback from the socialization participants. This is evidenced by the high enthusiasm of the participants by asking questions related to digital financial literacy and online loans and there are also participants who conduct consultations regarding problems with online loans.